Raloxifene therapy inhibits osteoclastogenesis during the alveolar healing process in rats - Luvizuto, Eloá Rodrigues [UNESP]; Dias, Sheila S. M. D. [UNESP]; Okamoto, Tetuo; Dornelles, Rita Cássia Menegati [UNESP]; Okamoto, Roberta [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Objective: To investigate the expression of OPG, RANKL and TRAP during alveolar healing process (7, 14, 21, 28 and 42 postoperative days) in ovariectomized rats treated with raloxifene or with oestrogen replacement therapy, using immunohistochemistry reaction approach.Materials and methods: Wistar female rats (10 weeks age) were submitted to ovariectomy surgery (OVX) or sham surgery. The female rats were divided in four groups: (1) sham; (2) OVX/O (ovariectomy and oil); (3) OVX/E2 (ovariectomy and oestrogen replacement); (4) OVX/RLX (ovariectomy and raloxifene therapy).Results: It was observed high amount of OPG immunolabelling with predominance at 14 and 21 postoperative days on sham and OVX/RLX groups, respectively. At 7 postoperative days, there was no difference between the groups for TRAP protein. Otherwise, to the other periods, it was observed greater expression of TRAP and RANKL protein on OVX/O group compared to sham, OVX/E2 and OVX/RLX groups. It was also observed a discrete TRAP immunolabelling at 28 and 42 postoperative days on OVX/RLX group.Conclusions: Oestrogen deficiency induces osteoclastogenesis in the alveolar healing process. Quantitative changes in the osteoclastic activity could be prevented through the raloxifene therapy. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Raloxifene; Bone; Osteoporosis; Oestrogen; Alveolar healing process; TRAP; RANKL; OPG; Ovariectomy; Osteoclasts; Osteoblasts